TensorExerciseSolutions - Tensor exercise - Solutions...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Tensor exercise - Solutions Problem 1: Although d I dt 6 = 0 in general, show that d I dt = 0 . Solution: Since I = 3 i =1 I i e i e i , and I i = 0, we have d I dt = X i ( I i e i e i + I i e i e i + I i e i e i ) = X i ( I i e i e i + I i e i e i ) = X i I i ( e i ) e i + I i e i ( e i ) . Now contract the left leg of each term with : d I dt = X i I i [ ( e i )] e i + I i ( e i )( e i ) . Each term in the equation is now just a vector. The first term on the right hand side vanishes [because ( e i ) = 0], but the second term does NOT vanish in general. (In the second term, we are taking the dot product of with e i , not with e i !) So d I dt = X i I i ( e i )( e i ) . Since ( e i ) is just a scalar, and ( e i ) = 0, each term on the right hand side of the above equation is a vector perpendicular to , so the whole expression d...
View Full Document

This note was uploaded on 01/22/2012 for the course PHYS 3202 taught by Professor Tan during the Spring '11 term at Georgia Institute of Technology.

Page1 / 2

TensorExerciseSolutions - Tensor exercise - Solutions...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online